POTENSIAL FOR DEVELOPING COFFEE PLANTATION IN GAYO LUES REGENCY - Fazlina, Yulia Dewi; Mikentona, Jorgi (RADJA PUBLIKA, 2025)
Gayo Lues Regency is one of the regencies in Aceh Province, Gayo Lues Regency is very strategic to be built and developed into a development area in the upstream part of Aceh and supports the development of the eastern and western regions of Aceh. This district has great potential in developing coffee commodities. The Director General of Horticulture, Ministry of Agriculture has proposed 3 (three) approaches to address the problem of climate change in coffee cultivation, one of which is a strategic approach (regional identification), in the form of an inventory of data and information related to areas that cultivate coffee. This study aims to identify and analyze the potential of land that can be developed into coffee plantations based on the suitability of the spatial pattern of the region. The method used is spatial analysis with an overlay approach between the existing coffee plantation map and the spatial pattern map, slope, and altitude. The results of the study show that of the total area of ​​Gayo Lues Regency, the land that has the potential to be developed as a coffee plantation is 57,521.66 hectares. This area is based on spatial analysis in accordance with the designation of spatial patterns based on the Gayo Lues Regency RTRW. The sub-district with the greatest development potential is Terangun Sub-district, while Blangpegayon Sub-district has the smallest potential of all sub-districts in Gayo Lues Regency. The results obtained can be the basis for determining the priority of development areas and planning a more targeted and effective coffee cultivation program.